2010
DOI: 10.5483/bmbrep.2010.43.1.034
|View full text |Cite
|
Sign up to set email alerts
|

OsAREB1, an ABRE-binding protein responding to ABA and glucose, has multiple functions in Arabidopsis

Abstract: Expression patterns of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Overexpressing OsbZIP23, a member of AREB/ABF subfamily can also significantly improve drought and high salinity resistance of transgenic rice at the reproductive stage . Enhanced tolerance to drought and heat was also observed in 35S-OsAREB1 transgenic Arabidopsis plants (Jin et al 2010). The over-expression of the constitutively active form of AREB1 in transgenic Arabidopsis plants showed ABA hypersensitivity and enhanced drought tolerance, and LEA-class genes and ABA-and dehydration-stress-inducible regulatory genes such as linker histone H1 and AAA ATPase were upregulated.…”
Section: The Areb/abf Regulonmentioning
confidence: 73%
“…Overexpressing OsbZIP23, a member of AREB/ABF subfamily can also significantly improve drought and high salinity resistance of transgenic rice at the reproductive stage . Enhanced tolerance to drought and heat was also observed in 35S-OsAREB1 transgenic Arabidopsis plants (Jin et al 2010). The over-expression of the constitutively active form of AREB1 in transgenic Arabidopsis plants showed ABA hypersensitivity and enhanced drought tolerance, and LEA-class genes and ABA-and dehydration-stress-inducible regulatory genes such as linker histone H1 and AAA ATPase were upregulated.…”
Section: The Areb/abf Regulonmentioning
confidence: 73%
“…However, unlike OsbZIP52 and OsABI5, it has been shown that OsbZIP46 functions as a positive regulator of abiotic stress through an ABA-dependent pathway (Hossain et al, 2010;Jin et al, 2010;Tang et al, 2012). OsbZIP46 as well as OsABF2, OsAREB1, and ABL1 are located at the same gene locus on chromosome 6 (Hossain et al, 2010;Jin et al, 2010;Yang et al, 2011;Tang et al, 2012).…”
Section: Roles In Response To Abiotic Stresses and Abscisic Acid (Aba)mentioning
confidence: 99%
“…OsbZIP46 as well as OsABF2, OsAREB1, and ABL1 are located at the same gene locus on chromosome 6 (Hossain et al, 2010;Jin et al, 2010;Yang et al, 2011;Tang et al, 2012). OsbZIP46 is an ABRE-binding protein that can be induced by multiple abiotic stresses such as drought, salinity, cold, and oxidative stress.…”
Section: Roles In Response To Abiotic Stresses and Abscisic Acid (Aba)mentioning
confidence: 99%
See 1 more Smart Citation
“…The yeast pPC87 expression plasmid was reconstructed from pPC86, which contains a galactose-inducible, protein-activating domain (GAL4) under the control of the yeast alcohol dehydrogenase (ADH1) promoter (23)(24)(25). Only pPC87 changed the enzyme sites to facilitate the Bam HI-Sac I ligation, and there was no other alteration.…”
Section: Yeast One-hybrid and β-Galactosidase Activity Assaymentioning
confidence: 99%